TRANSFORMASI KEPEMIMPINAN DIGITAL DALAM DOKTRIN PERTAHANAN: STUDI PERBANDINGAN RUSIA, AMERIKA SERIKAT, DAN ISRAEL SEBAGAI BASIS PENGUATAN PERTAHANAN SIBER INDONESIA - Petrus Bambang Setya Budi; Gatot Dwi Nugroho, Tarsisius Susilo, Gusti Bagus Oka Tapayasa, H.D. Arifin Simanjuntak (JOURNAL OF LAW AND NATION, 2026)
This study examines the transformation of digital leadership in defense doctrines, focusing on lessons from Russia, the United States, and Israel, and their implications for the urgency of establishing an Indonesian cyber defense doctrine. The research employs a literature-based approach through strategic comparative studies, policy analysis, and global benchmarking. Findings reveal that Russia emphasizes digital sovereignty through strategic information control; the United States prioritizes multisectoral collaboration and technological innovation; while Israel highlights leadership flexibility and the development of digital human capital. Benchmarking indicates that Indonesia should integrate these three approaches in formulating a national cyber defense doctrine rooted in Pancasila values, national interests, and the principle of state sovereignty. Therefore, the establishment of a cyber defense doctrine in Indonesia is a strategic necessity to strengthen national security, protect critical infrastructure, and develop adaptive digital leadership in the era of technological disruption.